2021
DOI: 10.3390/rs13081570
|View full text |Cite
|
Sign up to set email alerts
|

Surface Freshwater Fluxes in the Arctic and Subarctic Seas during Contrasting Years of High and Low Summer Sea Ice Extent

Abstract: Freshwater (FW) flux between the Arctic Ocean and adjacent waterways, predominantly driven by wind and oceanic currents, influences halocline stability and annual sea ice variability which further impacts global circulation and climate. The Arctic recently experienced anomalous years of high and low sea ice extent in the summers of 2013/2014 and 2012/2016, respectively. Here we investigate the interannual variability of oceanic surface FW flux in relation to spatial and temporal variability in sea ice concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 77 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…examined SMAP in the coastal waters of the Gulf of Maine and found the monthly SSS anomalies to be sufficiently accurate and applicable for coastal studies. Hall et al [2021] used SMAP and SMOS in the Arctic and found them to successfully capture sea ice extent and SSS variability, while Hackert et al [2019] demonstrated that including SMAP into the initialization of coupled model forecasts had positive impacts. Despite its quite extensive, successful applications in other seas and ocean basins, to date, and to the best of our knowledge, there has not been any dedicated study aimed at examining SSS variability from SMAP in the NWGoG.…”
Section: Introductionmentioning
confidence: 99%
“…examined SMAP in the coastal waters of the Gulf of Maine and found the monthly SSS anomalies to be sufficiently accurate and applicable for coastal studies. Hall et al [2021] used SMAP and SMOS in the Arctic and found them to successfully capture sea ice extent and SSS variability, while Hackert et al [2019] demonstrated that including SMAP into the initialization of coupled model forecasts had positive impacts. Despite its quite extensive, successful applications in other seas and ocean basins, to date, and to the best of our knowledge, there has not been any dedicated study aimed at examining SSS variability from SMAP in the NWGoG.…”
Section: Introductionmentioning
confidence: 99%
“…The 1/12°degree CMEMS GLORYS12V1 reanalysis (hereafter referred to as GLORYS12V1) (Lellouche et al, 2021) is used as a comparison dataset alongside the satellite products over the common observational periods (since 2011/2015) in this region (Table 1). This reanalysis is chosen for its high spatial resolution, its good representation of Arctic SIC, and its previous application to salinity variability in the Subpolar North Atlantic and Arctic (Biló et al, 2022;Hall et al, 2021;Lellouche et al, 2021;Liu et al, 2022). For consistency with the satellite SSS products, the GLORYS12V1 reanalysis is re-gridded onto a 0.25°grid for comparison with in situ data.…”
Section: Reanalysesmentioning
confidence: 99%
“…ECMWF's fifth-generation reanalysis of global weather and climate (ERA5) monthly eastward and northward turbulent surface stress is used in assessing the main drivers of Laptev Sea interannual variability (Hersbach et al, 2020). The monthly mean NCEI Climate Prediction Center (CPC) Arctic Oscillation Index (AOI) (https://www.ncei.noaa.gov/ access/monitoring/ao/, last access: 5 March 2024) is also used to relate local eastward wind stress patterns to largerscale atmospheric circulation.…”
Section: Reanalysesmentioning
confidence: 99%
“…This provides the maximum satellite data for comparison in September, and large variability in SSS to compare to ice extent. The two years 2016 and 2017 were the only two covered by every product compared, and as 2016 was a year of anomalously low ice, 2017 was chosen to compare the SSS and sea-ice extent to contrast some capabilities of the models [65]. ECCO is the only model simulation used here that assimilates satellite-derived salinity and uses the Aquarius product [39].…”
Section: Sea Surface Variability and Connection To Freshwatermentioning
confidence: 99%